Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/ange.200504599
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Induced Release of Encapsulated Materials inside Living Cells

Abstract: Fluchtweg: Die Laser‐initiierte Freisetzung von fluoreszenzmarkierten Polymeren aus Polyelektrolytmultischicht‐Mikrokapseln in lebenden Krebszellen wird vorgestellt. Ein Polymer wird in Kapseln eingeschlossen, die als Lichtabsorptionszentren fungierende Metallnanopartikel in den Wänden enthalten. Die Kapseln werden von Zellen aufgenommen, und Nah‐Infrarotlicht bricht die Kapselwände auf, sodass der Inhalt in die Zellen gelangt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
149
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 426 publications
(160 citation statements)
references
References 122 publications
5
149
0
5
Order By: Relevance
“…In recent times, the nanoparticles have become a passionate awareness in biomedical applications as they possess antifungal, anti-inflammatory, antiviral, and antibacterial actions (El-Badawy et al 2010;Zhong et al 2010). AgNPs have been extensively used for diagnosis treatment (Uchihara 2007;Sibbald et al 2007), coating on medical devices (Galiano et al 2008), drug delivery (Skirtach et al 2006), in wound dressing of (Moore 2006), contraceptive devices (Chen and Schluesener 2008) and medical textiles (Vigneshwaran et al 2007). Nanoparticles can be easily produced by various approaches which include chemical (Sun et al 2002), electrochemical (Yin et al 2003), radiation (Dimitrijevic et al 2001), photochemical and biological techniques (Naik et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, the nanoparticles have become a passionate awareness in biomedical applications as they possess antifungal, anti-inflammatory, antiviral, and antibacterial actions (El-Badawy et al 2010;Zhong et al 2010). AgNPs have been extensively used for diagnosis treatment (Uchihara 2007;Sibbald et al 2007), coating on medical devices (Galiano et al 2008), drug delivery (Skirtach et al 2006), in wound dressing of (Moore 2006), contraceptive devices (Chen and Schluesener 2008) and medical textiles (Vigneshwaran et al 2007). Nanoparticles can be easily produced by various approaches which include chemical (Sun et al 2002), electrochemical (Yin et al 2003), radiation (Dimitrijevic et al 2001), photochemical and biological techniques (Naik et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…17 However, many applications also require remote control over the permeability of the microcapsule shell. This can be done by light or laser irradiation, [18][19][20][21][22][23] alternating magnetic field, 24 microwave radiation 25 or ultrasound. [26][27][28] Considerable progress was achieved in the use of laser irradiation for microcapsule opening.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Considerable progress was achieved in the use of laser irradiation for microcapsule opening. 22,23 Usually, metal nanoparticles [19][20][21][22][23] or dyes 19 are used to provide microcapsule shell sensitivity to laser radiation. Our research has recently demonstrated that it is possible to release encapsulated materials inside living cells from laser-sensitive capsules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, their photo physical proper-ties could trigger drug release at remote place. 63 Drug delivery systems (DDSs) provide positive attributes to a 'free' drug by improving solubility, in vivo stability, and biodistribution. They can also alter unfavorable pharmacokinetics of some 'free' drugs.…”
Section: Gold Nanoparticle In Therapeuticsmentioning
confidence: 99%